Contesting and Curating the Queer African Archive with Sacred Queer Stories - Megan Robertson (African Journal of Gender and Religion (AJGR))
This roundtable was first convened as part of the 6th Es’kia Colloquium hosted by the Department of African Literature at Wits University, South Africa on the 15th and 16th September 2022. The discussion engages questions regarding knowledge production, method and (inter)textualities in relation to the book, Sacred Queer Stories: Ugandan LGBTQ+ Refugee Lives and the Bible (2021), co-authored by Adriaan van Klinken and Johanna Stiebert with Brian Sebyala aand Fredrick Hudson.